PENGARUH TEKNIK PQRST TERHADAP PEMAHAMAN MEMBACA SISWA KELAS DELAPAN SMPN 3 TAMBANG - Hopi, Nanda Parentsa; Aruan, Rumiri; ', Novitri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is aimed to find out whether there is a significant effect of using PQRST technique on students? reading comprehension at the eighth grade of SMPN 3 Tambang in descriptive text. This is a pre-experimental research conducted by using a pre-test ? treatment ? post-test design. This research used one group pre-test - post-test design. The instrument used in this research was multiple-choice tests (pre-test and post-test). The population of this research was 229 of the eighth grade students of SMPN 3 Tambang and the sample of this research is the VIII 3 of SMPN 3 Tambang which is total number of students of class is 33 students. The data of this research were collected by giving reading test on descriptive text (pre-test-post-test) to the students. The collected data were analyzed by using t-test formula. The results of data analysis showed the mean score of pre-test was 59.85, and the mean score of post-test was 68.71. Based on the data analysis, it can be concluded that there is a significant difference between the pre-test and the post-test because the t-test observed was higher than t-table. In other words, the alternative hypothesis of this research was accepted and null hypothesis was rejected. It also means that teaching reading by PQRST technique was effective to improve students? reading comprehension especially in descriptive text.